USING CONCESSIONAL TAXATION METHODS FOR INVESTMENT MARKETING PROJECTS IMPLEMENTING - E. Gulkova (Publishing House of the State University of Management, 2016)
Authors analyze problems of tax policy to stimulate investment activity of companies and suggest ways of developing tax legislation. Authors consider tax policy at conditions of investment activity increasing and introduction of innovations. Tax benefits are considered as one of the main instruments of tax policy. Authors offer to create and introduce the method of submitting tax benefits in the legislation of Russian Federation. The most typical problems of a complex economic assessment of tax optimization and collecting of taxes in Russian Federation are allocated. Authors take into consideration such important factor as investment marketing. Possibilities of investment marketingapplication in organizations, interrelation with taxes instruments are analyzed.